Effect of topical fluoride application on enamel after in‐office bleaching, as evaluated using a novel hardness tester and a transverse microradiography method. (7th November 2017) - Fukuyama, Mai; Kawamoto, Chiharu; Saikaew, Pipop; Matsuda, Yasuhiro; Carvalho, Ricardo M.; Selimovic, Denis; Sano, Hidehiko
Abstract : This study evaluated the effect of topical fluoride application on enamel hardness after in‐office bleaching. Twelve human incisors were cut along the long axis, resulting in 24 halves used in four treatment groups ( n = 6 in each group): (i) untreated group (C); (ii) in‐office bleaching material (B); (iii) treatment with surface reaction‐type prereacted glass‐ionomer varnish after in‐office bleaching (B+PRG); and (iv) treatment with acidulated phosphate fluoride solution after bleaching (B+F). All specimens were subjected to pH‐cycling for 4 wk. Knoop hardness was measured using a Cariotester. The decalcification of enamel was assessed quantitatively by measuring the integrated mineral loss (ΔIML). Games–Howell analysis was used to assess statistical significance of between‐group differences. The Knoop hardness decreased significantly after bleaching for all groups. In treatment groups B+PRG and B+F, the Knoop hardness returned to the original unbleached values after the first pH cycle and did not change afterwards. In treatment groups C and B there was a gradual decrease in the Knoop hardness until the fourth pH cycle. The integrated mineral loss, ΔIML, was significantly higher in treatment group B+F after 2 wk than in the other treatment groups. After 4 wk, the ΔIML in treatment group B was significantly higher than in treatment group B+PRG. The application of fluoride‐containing materials after bleaching results in recuperation of hardness to levels similar to those of unbleached enamel.